2014
DOI: 10.4103/0019-5278.134945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health education intervention on the awareness and use of personal protective equipments among small scale electric arc welders in Ilorin, Nigeria

Abstract: Introduction:Welding is associated with workplace hazards that can affect the health of those who engaged in it as they are exposed to harmful dust.Subjects and Methods:This was a health education intervention study carried out among self-employed electric arc welder. Data were collected using an interviewer administered questionnaire and health education intervention was carried out between the preintervention and postintervention stages. Epi-info version 3.5.1 software package was used for data analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 2 publications
2
22
0
Order By: Relevance
“…The study conducted by Adewoye et al in Nigeria indicated that educational intervention was effective on the use of various PPE, especially helmet in welders [23]. A systematic review of the published documents from 1980 to 2001 revealed that theoretical frameworks such as the TPB, the theory of reasoned action (TRA), and the health belief model (HBM) were effective on prevention of unwanted incidents through improved health behaviors of workers [10, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Adewoye et al in Nigeria indicated that educational intervention was effective on the use of various PPE, especially helmet in welders [23]. A systematic review of the published documents from 1980 to 2001 revealed that theoretical frameworks such as the TPB, the theory of reasoned action (TRA), and the health belief model (HBM) were effective on prevention of unwanted incidents through improved health behaviors of workers [10, 13].…”
Section: Discussionmentioning
confidence: 99%
“…16,19,20 In Nigeria, an intervention to educate welders about PPE use found a significant increase in the use of in PPE. 21 Hence education among welders on the importance of use of PPE can play a pivotal role in reducing injuries.…”
Section: 11mentioning
confidence: 99%
“…Similar to many other occupations welding technology may also pose hazards and risks (Santamaria et al, 2007;Adewoye et al, 2014;Wong et al, 2014).The potential hazards related to welding are exposure to toxic gases, metallic fumes, ultraviolet and infrared radiation (Gordon 2004). The most frequent A c c e p t e d M a n u s c r i p t 3 among all hazards is attributed to metal exposure especially in stainless steel welding process (Antonini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%